Postsekularny niepokój - Obirek, Stanisław (Humaniora. Czasopismo Internetowe, 2019)
The pretext to write the essay was contact with paintings and installations of Lech Twardowski, which arouse involuntary anxiety. You can see in them impatience with those trends in the humanities that are too sure of their arguments and are reluctant to open themselves to possible changes and corrections. Meanwhile, it should be the opposite. This principle should apply not only to artistic activities, but to all conceptualization efforts, especially in theology. It is theology, the science that deals with God and spirituality, is especially called to review its projects because it deals with matters that by their nature escape all concepts. Today we are witnessing a real eruption of new theological concepts. A particularly intriguing proposition has recently been proposed by Peter Phan, who has an interesting formula of “multiple religious belonging,” which in his opinion adequately describes the state of religious consciousness of the inhabitants of the Far East. This kind of thinking can be seen in post-secularism.